PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP TINGKAT KONSERVATISME AKUNTANSI - Nurlely Nasution (AKT 16 UMY 226, 2016)
this study aims to analyze the effect of the independent commissioner, managerial ownership, quality of the audit committee and board size on the level of accounting conservatism. The population of this research are all manufacturing companies listed in the Indonesia Stock Exchange as long as 2009-2013. The sampling selection technique used method was purposive sampling. During observation of years there are 110 companies qualified as samples. Data analysis techniques in this research using descriptive statistics, the hypothesis was tested using logistic regression analysis consisting of testing the feasibility of a regression model, assess the model fit, the coefficient of determination, classification matrix, and test the regression coefficients. Statistical test results showed that the population of independent commisioner and quality of the audit committee on the manufacturing companies has positive effect on the level of accounting conservatism, but managerial ownership and board size does not effect on the level of accounting conservatism. Keywords: The proportion of independent commissioners, Managerial Ownership, Quality of the Audit Committee, Board Size, Accounting Conservatism Level.